Effect of MnFe2O4 Nanoparticles to Reduce CO and HC Levels on Vehicle Exhaust Gas Emissions - Poppy Puspitasari; Sukarni Sukarni; Amir Hamzah (Universitas Negeri Malang, 2018)
The air pollution particle emitted from transportation in Indonesia Bay 2015 consist of 70.50% CO; 18.34% HC; 8.89% NOx; 0.88% SOx; 1.33%. These gases are very harmful to humans. To reduce the toxic gas effect, special treatment is needed, one of them is by applying catalyst on exhaust system. MnFe2O4 has the potential to bind the CO and HC elements contained in the exhaust gas. This study aims to investigate the effect of MnFe2O4 addition on catalityc converter towards CO gas and HC emissions of motor vehicles. Therefore, the percentage of exhaust reduction with and without applying MnFe2O4 on varied engine rotation using fuel with RON of 88, 90, 92 and 98 can be revealed. The results describe that the highest reduction precentage of CO content by applying MnFe2O4 nanoparticles as a catalyst for premium, pertalite and pertamax fuel are 34.1% (effective at low and high rotation); 31.1% (effective at all rotations); and 3.9% (effective at low rotation). On the other hand, the highest reduction percentage of HC content on premium, pertalite, pertamax and pertamax turbo fuel are 79.3% (effective in high rotation); 71.4% (effective at high rotation); 53,6% (effective in high rotation); and 2.1% (only effective at low rotation).